Uma outra Sonic Youth: a génese do barulho nas Caldas da Rainha - Moura, Luiz Alberto (2016)
This paper aims to cast a preliminary look at the initial moments of thenoise/experimental scene that rocked in the city of Caldas da Rainha, at the turn of the1980s to 1990, focusing on the artistic, musical and cultural activities of local bands -and having the artist João Paulo Feliciano as the protagonist. Thus, we have tried toidentify the key points and factors that enabled the flowering of a noise scene in Caldasda Rainha, with record stores, people, meeting points, publishing houses, concerts,live sessions, parties etc. It was also our aim to highlight the initial impact that thesemusic and artistic movements in this city had on the rest of the country. At the sametime, we present the points of influence that the rock effervescence in Portugal had inCaldas da Rainha and its noise/experimental scene, launching a preliminary analysisof the scene progress branches in the city that led local musicians, and Feliciano, to behighlighted at the national level. For that matter, this article tries to make a preparatoryessay from the scene concept to the dynamics developed in Caldas da Rainha,emphasising the need that certain actors felt for the creation of its own "ecosystem",which led them to create publishing houses, schedule gigs and expand the network,as well as characters and spaces that are so important for the independent scenes.Here, we add the importance of contacts with musicians from other cities of Portugaland even the ties of friendship between Feliciano and Lee Ranaldo (Sonic Youth) andhow it helped to legitimate the noise done in the city, more recognised by Tina and theTop Ten.